2013
DOI: 10.1007/s12026-013-8449-0
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic approaches for protecting hematopoietic stem cells in aplastic anemia

Abstract: Aplastic anemia (AA) is an immune-mediated and life-threatening form of acquired bone marrow failure (BMF), characterized by development and expansion of self-reactive T cells. These T cells cause continuous destruction of hematopoietic stem cells (HSCs), progenitors, and mature blood cells, leading to severe and if left untreated fatal marrow hypoplasia and pancytopenia. Standard treatment options for patients with AA include: (1) immunosuppressive therapy (IST) with anti-thymocyte globulin and cyclosporine A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The disorder of immune system especially T cells plays an important role in the development of AA. Therefore, immune reconstitution is very important in the treatment of AA (Weston et al, 2013). Our results showed that the oral administration of TSDN preparation caused a significant increase in the percentages of CD3 þ , T-helper cells (CD4 þ Th cells) and a decrease in the percentage of T-cytotoxic/ suppressor cells (CD8 þ Tc cells) in AA mice BMNC, respectively.…”
Section: Nipponica and Immunoregulationmentioning
confidence: 70%
“…The disorder of immune system especially T cells plays an important role in the development of AA. Therefore, immune reconstitution is very important in the treatment of AA (Weston et al, 2013). Our results showed that the oral administration of TSDN preparation caused a significant increase in the percentages of CD3 þ , T-helper cells (CD4 þ Th cells) and a decrease in the percentage of T-cytotoxic/ suppressor cells (CD8 þ Tc cells) in AA mice BMNC, respectively.…”
Section: Nipponica and Immunoregulationmentioning
confidence: 70%
“…Its causes are various, and it is regarded as an autoimmune disorder55 in which immune cells (mainly T cells)56 attack the bone marrow and cause pancytopenia. Its first-line treatment consists of hematopoietic cell transplantation and administration of immunosuppressive drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, IST approach is often not applicable due to poor response or relapse post IST. As with leukemia, bone marrow transplants are not an ideal option due to lack of histocompatible donor, age, comorbidities, etc (30)(31)(32). Maiguel et al (2011) have discovered a drug named leukadherins, which protects HSCs from self-reactive effector T cell in AA condition, thus reducing the loss of HSCs and its progenitor cells in immune-mediated AA, improving Figure 1.…”
Section: Aplastic Anemia (Aa)mentioning
confidence: 99%